TARP from the banks’ perspective: Evidence from conference calls - Helwege, Jean; Liu, Xin (Journal of Financial Intermediation, 2025)
Using earnings conference calls, we investigate banks’ views of the Troubled Asset Relief Program (TARP) to understand why TARP generated so few loans. We find that banks generally regarded TARP favorably and many mentioned using TARP funds to make loans. However, actual loan growth fell well below expectations based on prior capital ratios, even among banks that publicly committed to lending. Other banks highlighted that the funds would improve their capital ratios. We show that these perspectives are largely unrelated to banks’ ex-ante financial characteristics, but instead reflect the evolving conditions during the crisis period. These shifts are consistent with a large decline in the fraction of banks that commented on the favorable pricing of the preferred stock over time. Our findings suggest that banks primarily used TARP funds to strengthen capital ratios, partly driven by CEO career concerns. Weak loan demand and evolving market conditions also contributed to the sluggish loan growth following the TARP injections.